Penerapan Seni Kreatif Eco-Print Menggunakan Teknik Pounding pada Masyarakat Desa Talang Mulya - Sri Ilham Nasution; Liza Aulia Putri Sandea; Hana Putriana Putriana (GUYUB: Journal of Community Engagement, 2024)
The development of Talang Mulya Village as an agro-tourism area requires the optimal and sustainable management of its natural and human resources, emphasizing local wisdom. This community service program aims to empower women and teenagers by providing them with practical skills, including decorating tote bags using the eco-print technique with the pounding method. This study employed the Participatory Action Research (PAR) method with a mentoring approach. The results demonstrated an increase in participants’ creativity in selecting various types of leaves and flowers and arranging them to create aesthetically pleasing patterns on tote bags. This activity is expected to serve as an initial step toward enhancing community skills while supporting the agro-tourism potential of Talang Mulya Village